2020
DOI: 10.1097/md.0000000000022679
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gestational diabetes mellitus and interleukin 1beta gene polymorphisms in southwest of China

Abstract: Gestational diabetes mellitus (GDM) is a kind of chronic inflammatory condition with carbohydrate metabolism disorder. Interleukin-1beta (IL-1β) plays an important role in inflammatory response, but its role in GDM development remains unknown. The aim of this study was to analyze the association between Interleukin 1beta (IL1B) rs1143623 and rs16944 polymorphisms and susceptibility to GDM. In total, 300 pregnant women with GDM and 261 healthy pregnant women were included in the study. In both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Cytokines of the IL-1 family critically regulate the inflammatory response by controlling several inflammation processes ( 39 , 40 ). Both IL-1β and IL-18, which are classic pro-inflammatory cytokines of the IL-1 family, participate in the initiation of IR of GDM and type 2 DM ( 17-19 ). The production of IL-1β and IL-18 is regulated by the NLRP3 inflammasome in different types of tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines of the IL-1 family critically regulate the inflammatory response by controlling several inflammation processes ( 39 , 40 ). Both IL-1β and IL-18, which are classic pro-inflammatory cytokines of the IL-1 family, participate in the initiation of IR of GDM and type 2 DM ( 17-19 ). The production of IL-1β and IL-18 is regulated by the NLRP3 inflammasome in different types of tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)-1β and IL-18 are important inflammatory cytokines in the initiation of maternal IR during GDM (17)(18)(19). The animal experimental study by Schulze et al (20) reported that treatment with an anti-IL-1β antibody improved glucose-tolerance of GDM mice.…”
Section: Introductionmentioning
confidence: 99%